Foundations of comparative politics democracies of the modern world - Newton, Kenneth 1940-; Deth, Jan W. van 1950- (Cambridge textbooks in comparative politics, 2005)
This authoritative new introductory text covers the key concepts, theories and issues involved in the study of comparative politics. Focusing on democratic government, it covers all important topics in the field from constitutional design and institutions; through mass and elite politics, groups, parties, the media and governments; to policy making and implementation. The final chapter considers the future of the state and democracy in a globalising world. The authors draw on experiences and examples from around the world, and the book includes extensive supporting apparatus for students and teachers, including briefings, fact files, key terms, guides to further reading, and related websites. Each chapter ends with a section dealing with the major theoretical approaches to the subject. The aim is to give students a clear and comprehensive account of democratic politics and government at the start of the twenty first century